Autonomous Emergency Gliding Landing Guidance and Control of Tilt-Wing Electric Vertical Take-Off and Landing for Urban Air Mobility Missions Using Control Barrier Functions - Liqun Ma; Yangchen Ding; Jianzhong Yang (Aerospace)
Urban Air Mobility (UAM) aims to transform urban transportation through innovative applications of electric Vertical Take-Off and Landing (eVTOL) aircraft. This paper focuses on tilt-wing eVTOLs, which offer significant advantages in energy efficiency and operational versatility. However, their unique flight characteristics present challenges, particularly during emergency landings. To address this, we propose a novel control framework that utilizes control barrier functions (CBFs) to ensure safe landings within urban environments, characterized by numerous obstacles and varying conditions. By integrating trajectory generation, tracking, and attitude control under stringent safety constraints, our method prioritizes occupant safety while complying with FAA airworthiness standards. We illustrate the framework’s effectiveness through simulations, demonstrating its ability to guide eVTOLs to safe touchdowns despite power loss or other emergencies. This study not only advances the understanding of emergency landing mechanisms for eVTOLs but also contributes to the broader field of urban air traffic management, offering a foundation for future research and practical implementations of UAM. The innovative combination of CBFs and global optimization techniques sets a new precedent for resilient aircraft control in complex urban scenarios, paving the way for the safe integration of eVTOLs into everyday urban life.